Kesadaran Tokoh Leo Dalam Novel “Dan Hujan pun Berhenti” Karya Farida Susanty: Kajian Teori Carl Gustav Jung - Dasilva Fatur Raihan; Eva Dwi Kurniawan (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The novel "And the Rain Stopped" by Farida Susanty is a novel that tells the story of a man named Leo Strada who experiences depression and distrust of anyone. In this research, the author uses Carl Jung's psychoanalysis theory to analyze the novel. This research is qualitative research with descriptive method. Jung's psychoanalytic theory focuses on the concept of the unconscious and archetypes. The author finds that the novel "And the Rain Stopped" contains many archetypes that describe Leo Strada's experience in dealing with depression. The author also found that the novel describes Leo Strada's individuation process, which is his process of reaching psychological maturity. This study shows that Jung's theory of psychoanalysis can be used to analyze the novel "And the Rain Stopped". The theory can help us understand Leo Strada's experience in dealing with depression and his individuation process.